Consumo del Café en la Población de la Ciudad de Loja: Periodo de Estudio 2020 - Encarnación Erique, Richar Alcívar (2020)
In the present investigation as objectives, the characteristics and habits that condition consumption and the number of per-capita cups of coffee in the population of the city of Loja were determined. It was developed under a descriptive investigation with an analysis of the most important aspects that determine the consumption of coffee; Based on the 145,604 inhabitants in 2020 of the population of the city of Loja aged between 15 and 59 years. The importance of this research focuses on understanding the preferences and behaviors of consumers, thus improving the interaction between companies and consumers, allowing them to achieve a high impact on the marketing of coffee, as well as serving as a source of consultation for development of future research that contribute to the socio-economic development of the city of Loja. In the methodological design, descriptive research was used with a quantitative approach; Methods were used: scientific, when exposing the correlation between variables and in the analysis of statistical results; inductive, contrasting the information obtained with the historical references; analytical-synthetic, in drawing up conclusions and recommendations based on the results obtained. Techniques were applied: survey, by means of a questionnaire both in physical and digital form; and the documentary technique was used in the compilation of the documentation. Results, the preferred characteristic is the aroma: 26.27% students, 14.69% public employees, 12.71% private employees; the most important habits are: in income between $ 200 and $ 400 10.17% consume 2 cups / day; the correlation coefficient between the variables of Income and Amount of consumption / day is 0.07; consumption in the female gender: 21.75% by taste; 49.15% consume at home, 42.37% consume in the morning, the male gender: 21.75% by taste, 41.81% consume at home, 33.90% consume in the morning; Finally, it is concluded that, the variables that determine the consumption of coffee in the population of the city of Loja, in order of importance are: aroma, flavor, origin, family tradition, presentation and color; those that have the least influence are: quantity, ease of preparation, price, custom, seller and for being healthy. Likewise, the global consumption of coffee in the city of Loja is 289,974 cups of coffee per day, which results in a per-capita consumption in the population of the city of Loja of 2 cups of coffee per day.